2011
DOI: 10.1093/humrep/der249
|View full text |Cite
|
Sign up to set email alerts
|

Human meiotic progression and recombination are affected by Bisphenol A exposure during in vitro human oocyte development

Abstract: Our findings show that BPA concentrations of 1 µM or higher decrease the survival of human fetal oocytes in vitro, and concentrations of 10 µM or higher increase MLH1 foci number. MLH1 is considered a CO marker, and thus an increase in MLH1 foci could indicate an increase in COs in BPA-exposed oocytes. These data suggest that BPA can act as a toxic substance, which has particular implications for human females and the critical events of meiotic prophase, such as pairing-synapsis and recombination processes, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 68 publications
4
44
0
1
Order By: Relevance
“…Similary as in the aforementioned studies on rodents, cattle, and primates, an increased number of crossing over and degenerations in oocytes have been determined also in human oocytes cultivated in vitro in the presence of BPA (Brieno-Enriquez et al 2011). In connected studies it has been demonstrated that the exposure of human oocytes to BPA is linked to up-regulation of genes involved in meiotic processes connected to double strand breaks repair progression (Brieno-Enriquez et al 2012).…”
Section: Influences Of Bpa On Reproduction Of Femalessupporting
confidence: 63%
“…Similary as in the aforementioned studies on rodents, cattle, and primates, an increased number of crossing over and degenerations in oocytes have been determined also in human oocytes cultivated in vitro in the presence of BPA (Brieno-Enriquez et al 2011). In connected studies it has been demonstrated that the exposure of human oocytes to BPA is linked to up-regulation of genes involved in meiotic processes connected to double strand breaks repair progression (Brieno-Enriquez et al 2012).…”
Section: Influences Of Bpa On Reproduction Of Femalessupporting
confidence: 63%
“…These events are critical for the segregation of homologous chromosomes at the first meiotic division, and subtle BPA-induced disturbances during prophase increase the incidence of chromosomally abnormal eggs produced by the mature female mouse (19). Similar prophase disturbances have been reported in Caenorhabditis elegans (33) and in human fetal ovaries exposed in vitro (34), and expression studies in the mouse have provided evidence of corresponding changes in gene expression (35).…”
Section: Discussionsupporting
confidence: 53%
“…In the mouse, subtle changes induced by BPA during meiotic prophase lead to an age-independent increase in aneuploid eggs in the adult (19). Thus, the finding that BPA induces similar effects on female meiosis in the mouse, the nematode C. elegans (33), in cultured fragments of human fetal ovaries exposed in vitro (34), and now in the female rhesus monkey suggests that BPA induces prophase changes in a wide variety of eukaryotes. The implications for humans are troubling because the impact of these effects would not be manifested for a generation.…”
Section: Discussionmentioning
confidence: 96%
“…Brieño-Enriquez et al (2011, 2012) reported that BPA (1–30 μM) increased oocyte degeneration by impairing meiotic progression in cultured human fetal oocytes and that, similar to mouse studies, human fetal oocytes that progressed to prophase exhibited increased levels of recombination (MLH1 foci) and gene expression changes. BPA also increased methylation errors in differentially methylated regions of maternally imprinted genes of oocytes in cultured preantral follicles of C57/BL6xCBA/Ca mice (Trapphoff et al 2013).…”
Section: Early Oogenesis and Ovarian Follicle Formationmentioning
confidence: 77%